2002
DOI: 10.1536/jhj.43.607
|View full text |Cite
|
Sign up to set email alerts
|

<b>C-reactive Protein and Coronary Artery Disease</b>

Abstract: SUMMARYEvidence suggests that inflammation plays a key role in the pathogenesis of atherosclerosis. The chronic inflammatory process can develop to an acute clinical event by the induction of plaque rupture and therefore cause acute coronary syndromes.The aim of this study was to determine the serum levels of the circulating acute-phase reactant C-reactive protein (CRP), which is a sensitive indicator of inflammation, in patients with chronic stable coronary artery disease (CAD) and acute coronary syndromes (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 51 publications
6
42
0
6
Order By: Relevance
“…CRP, a factor in systemic inflammatory response, is relevant to the prognosis of KD patients with CAL (27). Serum CRP level is increased in patients with myocardial ischemia and sudden death due to coronary artery disease (28). Previous studies have shown that elevated ESR in KD patients is disadvantageous to the prognosis of CAL (29).…”
Section: Discussionmentioning
confidence: 99%
“…CRP, a factor in systemic inflammatory response, is relevant to the prognosis of KD patients with CAL (27). Serum CRP level is increased in patients with myocardial ischemia and sudden death due to coronary artery disease (28). Previous studies have shown that elevated ESR in KD patients is disadvantageous to the prognosis of CAL (29).…”
Section: Discussionmentioning
confidence: 99%
“…9,15,[20][21][22][23] Epidemiological studies have shown that CRP levels are a strong independent predictor of risk and an active pathogenic agent of future myocardial infarction, stroke, peripheral arterial disease, and vascular death among persons without known cardiovascular disease. 15) Possible mechanisms of cardiovascular dysfunction with increased levels of CRP have been described recently.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is found within atheromatous plaque, correlates with vascular dysfunction, and promotes the secretion of inflammatory mediators by vascular endothelium. 14,20,21,23) CRP itself induces adhesion molecules and the production of monocyte chemoattractant protein-1 in human endothelial cells and sensitizes endothelial cells to the cytotoxic process by CD4 + T cells. 24,25) We showed that the number of OSAS patients whose CRP levels were above the limits was significantly higher than for non-OSAS patients (5.3% of patients in non-OSAS group and 23.4% in OSAS groups had positive CRP (> 5 mg/L), P = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…27 Experimental studies have shown that short periods of ischemia followed by reperfusion elicit a cascade of pro inflammatory reactions that include production of oxygen-derived free radicals, activation of the complement system, adherence of the neutrophils to the coronary endothelium, leukocytemediated injury of the myocardial cells, and production of cytokines and acute phase proteins. 28 High sensitivity testing for CRP (hsCRP) has emerged as a convenient tool for detecting low-level systemic inflammation that portends a higher risk of developing atherothrombotic vascular disease in ostensibly healthy men and women and poor short-and long-term prognosis in patients after AMI. 29 American Heart Association guidelines risk stratifies people on the basis of the amount of CRP in blood.…”
Section: Resultsmentioning
confidence: 99%